Evaluación del efecto de la aplicación de enmiendas con dos fuentes de calcio, sobre el suelo y en el rendimiento de una mezcla forrajera en la Hacienda María Delfina, Cayambe - Herrera Pozo, Bryan Alexander (2022)
Gradually worldwide the fertility of the soils has been deteriorating, so, the soils of the northern zone have presented this detriment, an important feature that presents is the acidity of the same. The main causes have been natural actions and agricultural activities that over the years will further affect productive capacity. One of the main methods and the oldest is the use of calcium amendments, as they reduce the acidity of the soils, improve the structure and are a complement to fertilization. The main objective of this work was to evaluate the effect of the application of amendments, with two sources of calcium, on the soil, on the yield of a forage mixture. The site of the experiment was at hacienda María Delfina, in the canton of Cayambe, province of Pichincha. The research work consisted of the superficial application of calcium amendments, for which an experimental DBCA design of 4 treatments was developed (control, calcium sulfate, calcium carbonate + calcium sulfate, calcium carbonate). The dosage was based on the results of the soil analysis. The work carried out will have its benefits since it will be known the improvements that occurred in the soil system, the amount of kg Ms / ha, chemical and bromatological conformation of the forage mixture. The results obtained with the application of the aforementioned amendments are effective for the improvement of soils that have problems of acidity and compaction. The best treatment for the decrease in the acidity of the soil was the treatment based on calcium carbonate that from a pH of 5.3 reached a pH of 5.9\; while for the reduction of compaction from 9 to 24 cm deep the best amendments presented the treatments based on calcium carbonate and the mixture of calcium carbonate + calcium sulfate with a decompaction on average of 20 points the best was calcium carbonate + calcium sulfate reaching values of , likewise, in the increase of kilograms of dry matter an average of 3367.72 kg Ms/ha/cut was obtained in the amendment applied with calcium carbonate + calcium sulfate.